Dispositional Mindfulness: Its Impact on Customer Oriented Organizational Citizenship Behavior and Mediating Role of Servant Leadership - Puswiartika, Dhevy; Rusyda Hinduan, Zahrotur; Sulastiana, Marina; Harding, Diana (Opción, 2019)
Research on mindfulness has been growing in its scope with significant impact within organizational settings. This study investigated the effect of disposition- al mindfulness on Customer Oriented-Organizational Citizenship Behavior (CO-OCB). The relationship between mindfulness and CO-OCB is mediat- ing servant leadership as an individual factor. This study was an explanatory survey among supervisors of the railway transportation service provider in the Jakarta area with data obtained from a total of 357 participants using the dense sampling technique and self-report questionnaires. The data ana- lyzed by using Structural Equation Modelling with Lisrel 8.7 software. The result showed that mindfulness significantly influences CO-OCB, and servant leadership mediated the relationship between mindfulness and CO-OCB. The theoretical implication of this study was the empirical evidence regarding the mechanism that mediates the impact of mindfulness on workplace outcomes, in this case CO-OCB, with servant leadership as a potential mediating role. This study also contributed to the literature regarding mindfulness in an or- ganizational setting. The practical implication of this study suggests that the management of the railway transportation service provider can improve Cus- tomer Oriented Organizational Citizenship Behavior of the employees by ini- tiating programs that can increase mindfulness as well as servant leadership.